Layer-by-Layer CdS-Modified TiO2 Film Electrodes for Enhancing the Absorption and Energy Conversion Efficiency of Solar Cells - Ming Li; Yong Liu; Hai Wang; Wenxia Zhao; Hong Huang; Chaolun Liang; Youjun Deng; Hui Shen (International Journal of Photoenergy)
A layer-by-layer assemble method was used to fabricate CdS quantum dots (QDs) sensitized electrodes. Scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS), and transmission electron microscopy (TEM) have been utilized to characterize the samples. The absorption spectra and photovoltaic measurement confirmed that much more effective deposition of QDs in TiO2 matrix and much better power conversion performance were achieved for these multilayer electrodes compared with the ones fabricated by traditional single-layer assembly method.